Prognostic Value of B-Type Natriuretic Peptide in Hospitalized Patients with Pneumonia - Nagappa H. Handargal; Faisal Usman (Wolters Kluwer Medknow Publications, 2024)
Background: Pneumonia is a major medical problem and is foremost infectious cause of death in developed countries. A rapid and reliable predictor might aid physicians in identifying hospitalization, intensive care unit admission, and treatment changes. B-type natriuretic peptide (BNP) has consistently been observed to improve the diagnosis and management of hospitalized patients with pneumonia. This investigation aimed to study the importance of BNP in the assessment of severity of pneumonia in a tertiary care center in South India. Subjects and Methods: A hospital-based observational research was carried out on patients admitted during the period of September 2016 to July 2018 with sample size of 108. All patients satisfying the inclusion criteria were enrolled. Detailed clinical history and physical examination findings were noted. Diagnostic criteria symptoms were recorded following the standard protocol. BNP was measured using the double-antibody sandwich enzyme-linked immunosorbent assay. The statistical analyses were done using the statistical software R version 3.6.3 and MS Excel. Results: Out of 108 patients, 48 (44.44%) were female and 60 (55.56%) were male. Of these, 45 (41.67%) patients identified with community-acquired pneumonia, 27 (25%) with health-care-associated pneumonia, 26 (24.07%) with aspiration pneumonia, and 10 (9.26%) with pneumonia with comorbid conditions. BNP levels among survivors and nonsurvivors were 193.52 ± 124.93 and 413.08 ± 149.38 pg/ml, respectively. The total mortality was 13/108 (12.04%). Out of 13 patients, 12 (92.31%) nonsurvivors had BNP level ≥200 pg/ml and 1 (7.69%) had 100-200 pg/ml. Conclusion: BNP levels could be a useful single prognostic marker for pneumonia. BNP levels correlated with the clinical severity of pneumonia.